2021
DOI: 10.1186/s12915-021-01109-x
|View full text |Cite
|
Sign up to set email alerts
|

The ATPase SRCAP is associated with the mitotic apparatus, uncovering novel molecular aspects of Floating-Harbor syndrome

Abstract: Background A variety of human genetic diseases is known to be caused by mutations in genes encoding chromatin factors and epigenetic regulators, such as DNA or histone modifying enzymes and members of ATP-dependent chromatin remodeling complexes. Floating-Harbor syndrome is a rare genetic disease affecting human development caused by dominant truncating mutations in the SRCAP gene, which encodes the ATPase SRCAP, the core catalytic subunit of the homonymous chromatin-remodeling complex. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…In contrast, this is not observed upon VPS72 downregulation. These observations support previous findings where INO80 [ 70 ] and SRCAP [ 71 ] associate with the spindle apparatus and are required for proper mitotic progression. To our knowledge EP400 has not been linked to spindle function yet.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, this is not observed upon VPS72 downregulation. These observations support previous findings where INO80 [ 70 ] and SRCAP [ 71 ] associate with the spindle apparatus and are required for proper mitotic progression. To our knowledge EP400 has not been linked to spindle function yet.…”
Section: Resultssupporting
confidence: 92%
“…In a previous report, we have found that the ATPase SRCAP interacts with a plethora of cytokinesis regulators and positively controls their recruitment to the midbody [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…IN = input, IP = immunoprecipitation. Synchronization of the HeLa cells was performed according to Messina et al [ 31 ]. B Histograms showing the quantitative analysis of mislocalizations of cytokinesis regulators at the midbody in mocks and BAF53a or Tip60 depleted cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations